Factors Predicting The Decision of Using Emergency Medical Service among Relatives of Patients with Acute Stroke in Yothi Medical Innovation District - Kaewdee, Yuranan; Koshakri , Ruchanok; Rerlurnrit, Juntima (Journal of The Royal Thai Army Nurses, 2026)
This research is a predictive research design to study the ability to predict the perception of symptoms, experiences with emergency medical services and the availability of transportation on the decision to use emergency medical services among relatives of patients with acute stroke in the Yothi Innovation Community, Bangkok. The conceptual framework is based on PRECEDE-PROCEED model and a review of relevant literature. A total of 119 participants were selected as samples, comprising relatives of patients diagnosed with acute stroke symptoms in the Yothi Innovation Community. The research instrument was a questionnaire developed by the researcher, consisting of the following sections:1) General information; 2Perception of acute stroke symptoms; 3) Experience with emergency medical services; 4) Availability of transportation to the hospital; and 5) Decision to use emergency medical services. Data were collected between March – May 2024.The analysis was conducted using multiple regression. The results revealed that the perception of stroke symptoms and experiences with emergency medical services significantly predict the decision to use emergency medical services among relatives of patients with acute stroke in the Yothi Innovation Community, Bangkok. at a statistical significance level of .05, with an Adjusted R Square value of 0.339 (33.9%). The findings can inform efforts to educate the public on recognizing and raising awareness with acute stroke symptoms. Additionally, they can guide the planning and development of a high-quality emergency medical service system that meet standards.